LEGO Batman, the movie. DC super heroes unite - Burton, Jon, 1969-; Goodman, David A., 1962-; Bloom, Brian, 1970-; Paulsen, Rob, 1956-; Bailey, Laura, 1981-; Willingham, Travis; Schlatter, Charlie; Wahlgren, Kari, 1977-; Baker, Troy, 1976-; Brown, Clancy; Smith, Christopher Corey; Warner Premiere (Firm); et al. ([United States] : Warner Home Video, 2013)
When Bruce Wayne receives the man of the year award, fellow billionaire Lex Luthor becomes jealous and decides to run for President. To create the atmosphere for his type of fear-based politics Lex recruits the Joker to perfect a Black LEGO Destructor Ray which wreaks havoc on Gotham. As Lex destroys Batman's tech, Batman reluctantly turns to Superman for help.
Title from container.
Adaptation of the video game Lego Batman 2: DC super heroes.
Special features: All-new featurette, Building Batman; from the DC Comics vault, 3 bonus cartoons; a LEGO Batman stop-motion short; winning shorts from the LEGO DC Universe super heroes video contest.
Brian Bloom, Rob Paulsen, Laura Bailey, Travis Willingham, Charlie Schlatter, Kari Wahlgren, Troy Baker, Clancy Brown, Christopher Corey Smith.
DVD, widescreen presentation, dual layer, NTSC, region 1, Dolby Digital 5.1 surround sound.
English, French and Spanish dialogue; French and Spanish subtitles; English SDH.
Keywords: Batman -- (Fictitious character) -- Juvenile drama; Joker -- (Fictitious character) -- Juvenile drama; Superman -- (Fictitious character) -- Juvenile drama; LEGO toys -- Juvenile drama; Superheroes -- Juvenile drama; Crime -- Juvenile drama; Feature films; Children's films; Superhero films; Animated films